Skin disease in the elderly a color handbook - Evans, Colby Craig (Manson, 2012)
In this new color handbook, the authors deal systematically with those skin conditions that are particular to or more common in the elderly covering testing, diagnosis and treatment options. Given ageing populations the need for such a book is urgent. More and more elderly patients will seek care for a variety of skin conditions, ranging from eczema and psoriasis to benign lesions and skin cancers. For environmental and physiological reasons, all such conditions become more prevalent in the elderly and the effects of treatment more problematic. Following an initial chapter on how skin changes with age, the authors discuss in turn inflammatory, neoplastic, infectious and metabolic/nutritional diseases of the skin, plus skin signs of systemic disease in old age.